Transnational mourning: exploring the lived experiences of grief and bereavement among migrant families in uMlazi township in Durban, South Africa - Makandwa, Tackson; Naidu, Maheshvari (Well Testing Journal, 2025)
Death is without doubt one of the most critical events in the lives of people, no less so within the global south and cultural complex of Africa and African (transnational) people. While it is individual, it is essentially a collective experience, arguably even more so for translocated African migrant communities. For migrants, the death of relatives, friends, or loved ones across national borders can complicate the process of bereavement, grief, and handling the remains of the dead. Drawing from in-depth qualitative research findings, this paper explores the lived experiences of grief and bereavement among transnational migrant families living in the uMlazi township in Durban, South Africa. Working through the theoretical lenses of transnational framework, ritual theory and disenfranchised grief, the paper identifies four interrelated themes; isolation in death and dying among strangers, community solidarity and institutional mediation of death, hybrid mourning practices, and the prolonging of sorrow and suffering brought by translocated spaces. The findings illustrate the dynamics around how mourning among migrants extends beyond the immediate moment of death, becoming an ongoing negotiation shaped by cultural obligations, bureaucratic hurdles, economic precarity, and the limits of belonging in host societies. Rooted in transnationalism, ritual theory, and the notion of disenfranchised sorrow, in this paper, we illustrate that death, in this setting, becomes not only a site of emotional expression but also a mirror reflecting the broader structural inequalities faced by migrants in urban South Africa. The study argues that migrant death highlights the fragility and resilience of transnational social fields, where mourning practices are simultaneously fractured by distance and reconstructed through solidarity.